Corruption – Why do they do it? - Othman, Zaleha; Shafie, Rohami; Abdul Hamid, Fathilatul Zakimi (Elsevier Ltd., 2014)
The Corruption Perception Index (CPI) for Malaysia shows undesirable results, indicating the issue of corruption should be taken seriously. To address the corruption issue social constructionist perspective is employed, specifically qualitative methodology is used to gain an insight of the phenomenon.This qualitative study investigates the factors contributing to the occurrence of corruption in the Malaysian context.A total of twelve interviews were conducted.The respondents in the study were practitioners, representatives from government agencies and senior public sector officials.Several themes emerged as to why people are corrupt, including: power, opportunity and moral impurity.This study suggests determinants of individual acts of corruption in the Malaysian context.The findings will be useful for practitioners and regulators as the findings can provide insightful information to support the proactive measure to fight corruption.